Data Analytics to Examine Trending Topics for Indonesian Election 2019 - Firman Arifin; Muhammad Hariadi; I Ketut Eddy Purnama; Budi Nur Iman; Elly Purwantini; Muhammad Anshari (Jurnal Inovtek Polbeng Seri Informatika, 2019)
Understanding public interest and opinion are necessary tasks in high intense political competition. Utilizing big data analytics from social media provide an important source of information that candidates can utilize, manage and even engage them in targeted political campaigning agenda. One of the source in big data is social media’s interactions. Social media empowers public to participate proactivelyin the campaigning activities. This paper examines trends gathered from data analytics of two contenders’ group for Indonesian Election in 2019. It tracks the recent patterns of people engagement via social media analytic specifically Twitter. The study developed the analysis into the proposed model based on their trends and patterns.